Examining the introduction and expiration price effect of warrants on their underlying assets: evidence from the Johannesburg Stock Exchange - Gumede, Lungelo Linda (Research of GSB, 2018)
The aim of this paper is to examine the price effect exerted by derivative warrants on their underlying shares around the introduction and expiration days of the warrants. The study is based on the JSE for the period 2008-2012 and employs the event study methodology. The study assesses the effects generally and for puts and calls separately. Overall, it is found that the price effect depends on the type of warrant as well as the warrant's "moneyness". The in the money sample of puts and calls show significant price effects around the listing and expiration days respectively. The out the money sample of puts and calls indicate no price effect. Each of the samples is subjected to further volume analysis in order to assert if the price effects are linked to any changes in trading volume. This paper has implications for the regulation community and warrant investors on the JSE.